2018
DOI: 10.1182/blood-2018-99-111946
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Myeloproliferative Neoplasms - Research Consortium (MPN-RC) 112 Randomized Trial of Pegylated Interferon Alfa-2a (PEG) Versus Hydroxyurea (HU) Therapy for the Treatment of High Risk Polycythemia Vera (PV) and High Risk Essential Thrombocythemia (ET)

Abstract: Introduction HU is the treatment of choice for patients (pts) with high risk ET/PV, however, PEG has been proposed as an alternative option due to its proposed potential to modify disease course. An interim analysis of MPN-RC 112 (Blood 2016 128:479;) did not reveal a difference in PR/CR rates between HU and PEG therapy after 12 months in the first evaluable 75 pts treated. Here we present the results and long-term follow-up of all pts participating in this pivotal study [NCT01259856]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
26
1
Order By: Relevance
“…Late autoimmune toxicities such as hypothyroidism, vasculitis, or hepatitis can also occur. When compared to hydroxyurea in MPD-RC-112 and DALIAH, grade 3/4 adverse events were significantly higher in pegylated interferon [47,49]. Discontinuation rates of pegylated interferon are still typically less than that of standard interferon, occurring in approximately 15-20% of patients on clinical trial [43,47,52], although in DALIAH, toxicity-dependent discontinuation was significantly increased in pegylated interferon (27%) compared to hydroxyurea (5%) [49].…”
Section: Essential Thrombocythemia and Polycythemia Veramentioning
confidence: 97%
See 1 more Smart Citation
“…Late autoimmune toxicities such as hypothyroidism, vasculitis, or hepatitis can also occur. When compared to hydroxyurea in MPD-RC-112 and DALIAH, grade 3/4 adverse events were significantly higher in pegylated interferon [47,49]. Discontinuation rates of pegylated interferon are still typically less than that of standard interferon, occurring in approximately 15-20% of patients on clinical trial [43,47,52], although in DALIAH, toxicity-dependent discontinuation was significantly increased in pegylated interferon (27%) compared to hydroxyurea (5%) [49].…”
Section: Essential Thrombocythemia and Polycythemia Veramentioning
confidence: 97%
“…Recently, results from randomized trials comparing pegylated interferon head-to-head with hydroxyurea have been reported. MPN-RC-112 was a Phase III trial that randomized high-risk ET/PV patients to first-line treatment with either pegylated interferon alfa-2a or hydroxyurea (Table 2) [47,48]. The overall response rate of 78% with pegylated interferon was not significantly different from the overall response rate of 70% in hydroxyurea-treated patients.…”
Section: Essential Thrombocythemia and Polycythemia Veramentioning
confidence: 99%
“…Results of the final analysis of the Myeloproliferative Disorders Research Consortium (MPD-RC) 112 global phase III trial of pegylated interferon alfa-2a ( n = 82) versus HU ( n = 86) in previously untreated patients (HU for <3 months permitted) with high-risk PV or ET (defined according to the 2008 WHO criteria, disease duration <5 years) were recently presented. 46 There were no significant differences between the treatment arms in terms of complete or overall response rates (ORRs) at 12 or 24 months. Interestingly, achievement of a complete hematologic response (CHR) was associated with worsening of some symptom and quality of life parameters.…”
Section: Updates In Therapymentioning
confidence: 91%
“…Bone marrow pathologic responses were more frequently observed in patients with ET, but there was no significant difference between the two treatment arms. 46 The phase III DALIAH trial compared recombinant interferon alfa (-2a or -2b, n = 35) to HU ( n = 21) in PV patients over 60 years of age. 48 The CHR rate at 36 months was significantly higher in the interferon group (49% versus 19%, p = 0.045), but the rates of hematocrit control and molecular response (all partial) were not.…”
Section: Updates In Therapymentioning
confidence: 99%
“…Previously, the Myeloproliferative Disorders Research Consortium (MPD-RC) 112 study and MPD-RC 111 study have highlighted the activity of IFNα in treatmentnaïve and HU-resistant/refractory ET/PV patients, respectively [26,30]. Most recently, phase III randomized controlled trials, PROUD-PV and its extension study CONTINUATION-PV, evaluated ropeg against HU in patients with PV.…”
Section: Agents In Clinical Development In Pv and Etmentioning
confidence: 99%